2008
DOI: 10.5194/bgd-5-903-2008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Carbon isotope discrimination of C3 vegetation in Central Asian Grassland as related to long-term and short-term precipitation patterns

Abstract: The relationship between carbon isotope discrimination ( 13 ) of C3 vegetation and long-term (30 years) and short-term (growing period) precipitation was investigated. Different species of Stipa, a dominant grass genus in the (semi-)arid Asian steppes, and other C3 species were collected along aridity gradients in Inner Mongolia in 2005 (11 sites, 71 samples) and in the Republic of Mongolia in 2006 (40 sites, 45 samples). The data set was expanded with published and unpublished data of Stipa and other C3 speci… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 46 publications
(47 reference statements)
2
21
0
Order By: Relevance
“…However, Wittmer et al [53] found that there was no relationship between foliar δ 13 C and foliar C/N. Our findings suggest that plants on the Qinghai-Tibet Plateau that have higher WUE may also have higher NUE, and on the basis of the significant correlation between δ 13 C and C/P for all samples and Stipa (Table 3), also have higher phosphorus use efficiency (PUE).…”
Section: Discussionmentioning
confidence: 43%
“…However, Wittmer et al [53] found that there was no relationship between foliar δ 13 C and foliar C/N. Our findings suggest that plants on the Qinghai-Tibet Plateau that have higher WUE may also have higher NUE, and on the basis of the significant correlation between δ 13 C and C/P for all samples and Stipa (Table 3), also have higher phosphorus use efficiency (PUE).…”
Section: Discussionmentioning
confidence: 43%
“…13Δc was calculated as 13Δwool +3.2‰, the constant fractionation between vegetation and wool [14]. Site-specific 13Δ3 was estimated from year-specific growing-season precipitation, PG in mm d−1, according to [24] and altitude, A in m above sea level, according to [25] asand 13Δ4 was taken as a constant 7.2‰ from [12]. The relatively high 13Δ4 is mainly caused by C. squarrosa, which dominates the C4 community and which has a high leakiness affecting 13Δ [26].…”
Section: Methodsmentioning
confidence: 99%
“…Growing season precipitation was geostatistically determined according to Wittmer et al (2008) for each sampling location and time of sampling. This was done by interpolating between meteorological stations and taking into account 1.5×1.5 km 2 resolution maps of MAP, mean monthly precipitation, MJulT, and MAT (Climate Source, Inc., Corvallis, OR, USA).…”
Section: Meteorological Data and δ13c Of Atmospheric Co2mentioning
confidence: 99%
“…Carbon isotope composition and nitrogen content were then measured using an elemental analyser (NA 1110; Carlo Erba, Milan, Italy) interfaced (ConFlo III; Finnigan MAT, Bremen, Germany) to an isotope ratio mass spectrometer (Delta Plus; Finnigan MAT) following the protocol by Wittmer et al (2008). Carbon isotope data were specified as δ 13 C relative to the Vienna Pee Dee Belemnite standard:…”
Section: Isotope and Nleaf Analysismentioning
confidence: 99%
See 1 more Smart Citation